The Effect of Portfolio Assessment on Iranian EFL Learners’ Writing Ability - Zahra Fattah (International Journal of Practical and Pedagogical Issues in English Education)
Much criticism of the traditional methods of assessment has been presented in the literature along with convincing arguments in favor of a need for alternative methods of assessment. Therefore, the aim of this study was to investigate the effects of a new form of assessment called Portfolio Assessment on promotion of the writing ability of Iranian EFL high school students. Two groups of high school students served as the subjects of the study. One group served as the experimental group and the other group as the control group. They attended writing classes two days a week, one hour a day. The experimental group received the special treatment which was the use of portfolio assessment during a ten-week period, while no treatment was given to the control group. The control group was managed by the ordinary method of teaching and evaluation. At the end of the experiment, a test of writing composition was administered to both groups. The experimental group performed significantly better than the control group. The results of the study showed that portfolio assessment had a positive effect on improving the writing ability of the experimental group.